Development of a UPLC-MS/MS method for establishing Serra da Estrela´s free amino acids profile - Santos, Andréia O. (2019)
Associate Laboratory LSRE-LCM-UID/EQU/50020/2019,strategic funding UID/BIO/04469/2019-CEB and BioTecNorte operation (NORTE-01-0145-FEDER-000004), strategic project PEst-OE/AGR/UI0690/2014–CIMOand by Project 02/SAICT/ 2016/23290-QCLASSE, funded by national funds through FCT/MCTES (PIDDAC)